2017
DOI: 10.1016/j.joca.2016.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and longitudinal study of the impact of posterior meniscus horn lesions on adjacent cartilage composition, patient-reported outcomes and gait biomechanics in subjects without radiographic osteoarthritis

Abstract: Individuals with healthy cartilage and posterior meniscal horn lesions have increased relaxation times when compared to matched controls, increased relaxation time changes over 2 years, and consistently report a lower KOOS QOL, yet show no difference in gait biomechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…In the later study, mechanical tests revealed a 19% increase in tibial articular cartilage thickness 3 months after injury and this supports our finding of a 14% increase in thickness (calculated as a mean increase in thickness of 0.4 mm relative to a mean 2.8 mm thick cartilage obtained from normal knees at the same location). Our measurements were taken soon after injury (mean 17 days) and are concerning as there is a strong evidence that the articular cartilage and its matrix components change soon after ACL injury, reconstruction and return to activity . In addition, following severe knee trauma that involves the ACL, increased T1ρ and T2 relaxation times are thought to reflect loss of proteoglycan and change in water content that precede changes to cartilage thickness associated with the progression of PTOA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the later study, mechanical tests revealed a 19% increase in tibial articular cartilage thickness 3 months after injury and this supports our finding of a 14% increase in thickness (calculated as a mean increase in thickness of 0.4 mm relative to a mean 2.8 mm thick cartilage obtained from normal knees at the same location). Our measurements were taken soon after injury (mean 17 days) and are concerning as there is a strong evidence that the articular cartilage and its matrix components change soon after ACL injury, reconstruction and return to activity . In addition, following severe knee trauma that involves the ACL, increased T1ρ and T2 relaxation times are thought to reflect loss of proteoglycan and change in water content that precede changes to cartilage thickness associated with the progression of PTOA.…”
Section: Discussionmentioning
confidence: 99%
“…Our measurements were taken soon after injury (mean 17 days) and are concerning as there is a strong evidence that the articular cartilage and its matrix components change soon after ACL injury, reconstruction and return to activity. 23,[35][36][37][38][39][40] In addition, following severe knee trauma that involves the ACL, increased T1ρ and T2 relaxation times are thought to reflect loss of proteoglycan and change in water content that precede changes to cartilage thickness associated with the progression of PTOA. This may be the underlying mechanism associated with cartilage thickening that was observed in the current study.…”
mentioning
confidence: 99%
“…Similarly, biological events such as cellular activation of the proinflammatory/protease cascades in either tissue or the joint may upregulate degradation of their extracellular matrices. A recent 3‐year longitudinal study, employing quantitative MRI (3T), imaged human patients with posterior meniscal horn lesions but no radiographic OA or MRI cartilage lesions at study entry . The investigators detected elevated cartilage relaxation times, reflecting matrix degeneration, adjacent to the meniscal lesions at the medial tibial plateau at 2 years, but not in matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated an association with structural lesions of the PHMED and tibial cartilage T1r/T2 values in ACLinjured patients but none have looked at the direct association between the T1r/T2 values of the meniscus and those of tibial cartilage 20,21 . In accordance with previous studies in patients who have already developed osteoarthritis, we show a significant positive correlation with baseline T1r/T2 relaxation times in the PHMED and 2-year T1r/T2 relaxation times in the MT 15,16 .…”
Section: Relationship Of Meniscus T1r/t2 To Cartilage T1r/t2mentioning
confidence: 99%
“…While longitudinal changes in T1r/T2 relaxation times in knee cartilage following ACL-injury are widely documented, it is unclear whether longitudinal change occurs in the meniscus and whether these possible changes vary by the location 11,18,19 . In addition, while studies have demonstrated the relationship between gross morphologic changes of the meniscus and T1r/T2 relaxation times of articular cartilage, it is unclear whether a relationship exists between T1r/T2 relaxation times of the meniscus and those of articular cartilage 20,21 .…”
Section: Introductionmentioning
confidence: 99%